Futuristic Strategic Planning for the Sustainability of Islamic Educational Institutions in Indonesia’s Digital Era - Debi Tiara Wulan Dari; Sri Uswatun Hasanah; Muhammad Sirozi (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to construct an integrated Futuristic Strategic Planning framework designed to ensure the sustainability of Islamic educational institutions amidst the disruptions of Indonesia’s digital era. A qualitative library research design was employed, utilizing Reflexive Thematic Analysis (TA) to examine authoritative academic documents, policy frameworks, and recent scholarly discourses published between 2015 and 2025. The research identifies three core components of futuristic planning: environmental scanning, trend analysis, and scenario building. These elements facilitate the “Mimbar to Mouse” digital transition, ensuring that technological adoption including AI and Learning Management Systems is systematically aligned with institutional identity. The findings indicate that futuristic planning shifts management from administrative compliance to a dynamic “foresight culture.” The novelty of this research lies in its unique synthesis of proactive foresight models with traditional Islamic pedagogical values, a combination often fragmented in previous literature. Practically, this study provides a strategic roadmap for educational leaders to optimize human resource planning and policy formulation, enabling them to remain resilient in a volatile global landscape. Theoretically, it expands the discourse on Islamic educational management by repositioning planning as the central mechanism for long-term sustainability. The study concludes that an integrated futuristic orientation allows Islamic institutions to remain globally competitive while maintaining their spiritual integrity.